2004
DOI: 10.1111/j.1600-079x.2004.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces dimethylnitrosamine‐induced liver fibrosis in rats

Abstract: Increased deposition of the extracellular matrix components, particularly collagen, is a central phenomenon in liver fibrosis. Stellate cells, the central mediators in the pathogenesis of fibrosis are activated by free radicals, and synthesize collagen. Melatonin is a potent physiological scavenger of hydroxyl radicals. Melatonin has also been shown to be involved in the inhibitory regulation of collagen content in tissues. At present, no effective treatment of liver fibrosis is available for clinical use. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 57 publications
5
65
0
Order By: Relevance
“…Cunnane et al [31] demonstrated that primary biliary cirrhosis is related with melatonin deficiency in pinealectomized rats. Tahan et al [12] reported that daily melatonin injection at pharmacological doses is effective against liver damage in a rat liver fibrosis model induced by a 14-d dimethylnitrosamine regimen. In the present study, liver injury was assessed with histological and biochemical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cunnane et al [31] demonstrated that primary biliary cirrhosis is related with melatonin deficiency in pinealectomized rats. Tahan et al [12] reported that daily melatonin injection at pharmacological doses is effective against liver damage in a rat liver fibrosis model induced by a 14-d dimethylnitrosamine regimen. In the present study, liver injury was assessed with histological and biochemical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo experiments have shown that melatonin can protect cells, tissues, and organs against oxidative damage induced by a variety of free-radical-generating agents and processes, such as safrole, lipopolysaccharide (LPS), carbon tetrachloride (CCl 4 ), ischemia-reperfusion, amyloid-protein, and ionizing radiation [10][11][12] . In addition, melatonin also has an indirect antioxidant effect by enhancing the levels of potential antioxidants such as glutathione peroxidase (GPx), superoxide dismutase (SOD), and glutathione (GSH) [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin is a versatile molecule endowed with an abrogated activation of HSCs induced by reactive oxygen species in vitro, 10 and different studies have shown that the pineal hormone prevents liver damage in rats with fibrosis induced by bile duct ligation, 11 dimethylnitrosamine, 12 or thioacetamide. 13 The most commonly used approach to cause experimental liver fibrosis is the periodic administration of carbon tetrachloride (CCl 4 ) in mice or rats.…”
mentioning
confidence: 99%